Assessing the investment viability of Indonesia's upstream electric vehicle (EV) sector stocks amidst the COVID-19 pandemic - Patria, Harry; Rahim, Djuwita A.; Hermawan, Heri; Prasetyo, Heru Budi (University of Islam Malang, 2023)
Amidst the global push for sustainability, the burgeoning electric vehicle (EV) industry has driven increased demand for batteries, placing the Indonesian nickel ore sector in a pivotal position due to its vast reserves. This study thoroughly examines the investment landscape of this sector, utilizing advanced portfolio optimization techniques to analyze four major nickel ore mine firms in Indonesia. Through Monte Carlo simulations, the study evaluates the optimal portfolios of risky assets, comparing their performance before and during the COVID-19 pandemic. Findings reveal a significant shift in portfolio composition during the Pandemic, reflecting investors' response to global disruptions by diversifying their holdings. Notably, the Sharpe Ratio, a risk-adjusted return measure, demonstrates an impressive increase in return relative to risk during the Pandemic, emphasizing the sector's resilience and attractiveness for investment, especially in times of economic uncertainty like the COVID-19 pandemic. The transformation in portfolio weights and the corresponding increase in risk-adjusted returns highlight the sector’s potential as a lucrative investment avenue, especially during periods of global economic uncertainty like the COVID-19 pandemic.